Deep Earth volatile cycles as revealed by basalt chemistry - Matthews, Simon William (St Catharine's, 2019)
Earth’s volatiles (e.g. CO$_2$ and H$_2$O) are thought to be stored largely in the interior of the planet. The partitioning of these volatile elements between Earth’s surface and interior controls the evolution of our atmosphere and oceans, acting as a regulator on our planet’s long term climate. Basalt geochemistry is our most direct probe of Earth’s convecting mantle, however the tendency of volatile elements to form vapour phases deep within volcanic systems obscures the mantle volatile signals inherited by basalts. This thesis explores the extent to which basalts may preserve mantle volatile signals, places new constraints on volatile heterogeneity within the Icelandic plume, and considers the role of mantle convection in establishing deep Earth volatile cycles. Volatile- trace element systematics in suites of basaltic glass and melt inclusions have been widely used to infer volatile abundances in the depleted mantle, but have resulted in a large diversity of estimates. In this thesis a new statistical treatment of such datasets is developed, using simple numerical models for concurrent magma mixing and degassing. It is demonstrated that the role of magma degassing was previously underestimated, and the variability in apparent mantle volatile concentrations is largely a result of variability in magma mixing and degassing. Using a large new dataset of Icelandic melt inclusions sampling diverse mantle components, alongside a compilation of existing suites, the gross structure of the global melt inclusion array is shown to be controlled by magma degassing and olivine decrepitation. By applying the new statistical treatment of the data developed here, the presence of at least three mantle components with distinct volatile chemistry are demonstrated to contribute Icelandic magmas. With a novel combination of geophysical and geochemical constraints, the thermal structure and mineralogy of the melting region beneath Iceland is constrained. The role of mineralogical heterogeneity in the long term storage of mantle ...